PENGARUH KOMUNIKASI TERAPEUTIK TERHADAP TINGKAT KECEMASAN IBU HAMIL TRIMESTER III DI KLINIK BERSALIN HJ. RISMALA - Dey, Titin Novayanti; Ginting, Luci Riani; Turnip, Meria (JURNAL HEALTH REPRODUCTIVE, 2021)
Therapeutic communication is an interpersonal relationship between health workers and clients in this relationship both of whom gain shared experiences in order to improve the emotional experience of clients. So the essence of therapeutic communication is a relationship that is carried out for therapeutic purposes. This research is a quantitative study with a quasi-experimental/quasi-experimental approach with a research design using pre-test and post-test. Determination of the number of samples using purposive sampling method and obtained a sample of 30 workers. Data was collected by interview using questionnaires and observation sheets. The independent variable in this study is Therapeutic Communication, while the dependent variable is compliance with the use of Anxiety Levels. Anxiety Level Compliance Assessment is in the good category (82.3%). Statistical test using T-Test with = 0.05. The results of the analysis show that there is an influence of therapeutic communication on the level of anxiety of pregnant women in the third trimester at the Maternity Clinic Hj. Rismala in 2021, with a p value (0.001 0.05). The conclusion of this study is that there is an effect of therapeutic communication on the level of anxiety in third trimester pregnant women.